Uji Aktivitas Antibakteri Ekstrak Etanol Tanaman Obat Suku Musi di Kabupaten Musi Banyuasin, Sumatera Selatan - Muharni, Muharni; Fitrya, Fitrya; Farida, Sofa (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2017)
Musi tribe community used medicinal plants generally based on cultural heritage. Unproper use of medicinal plants unproperly cause the drug does not work effectively. Ten medicinal plants were selected for antibacterial activity tested using disc diffusion method against two testb bacteria i.e Escherichia coli (E. coli) and Staphylococcus aureus(S. aureus) at concentrations of 125, 250, 500, and 1000 μg/mL. Minimum inhibitory concentration (MIC) were determined for the active extract which still gives antibacterial activity using well method. The result showed only three test extracts, i.e Coleus scutellarioides, Blumea balsamifera and Lantana camara gave inhibition zone diameter of 11-20 mm against E. coli. Meanwhile, four extracts i.e Coleus scutellarioides, Blumea balsamifera, Dillenia alata and Dimocarpus melayensis gave inhibition zone diameter of 11-20 mm against S. aureus. Determination of MIC values for Coleus scutellarioides and Blumea balsamifera extracts gave the same MIC value of 125 μg/mL for both test bacteria. Meanwhile, Lantana camara gave MIC value of 250 ug/mL for E. coli. Dillenia alata and Dimocarpus melayensis also provide MIC value of 125 ug/mL againts E. Coli. It was found that there were five active extracts among ten extracts tested. Two extracts which active against both test bacteria were Coleus scutellarioides and Blumea balsamifera. One extract, Lantana camara only active against E. coli and the two others Dillenia alata and Dimocarpus melayensis were active against S. auerus.